Utilization of Traditional Art Damar Kurung from Gresik as A Mathematics Learning Media to Improve Understanding of The Volume Concept in Elementary School Students - Arianti, Dini; Gunansyah, Ganes; Mariana, Neni (IKIP PGRI Bojonegoro, 2025)
This study aims to explore the use of traditional Damar Kurung art from Gresik as a medium for learning mathematics to improve the understanding of the concept of volume in elementary school students. Damar Kurung art, known as a three-dimensional wood carving art, was chosen as a learning aid to visualize the concept of volume in real terms. This study uses a qualitative approach with a case study method involving observation, interviews, and documentation in the classroom that applies Damar Kurung art as a medium for learning mathematics. The results of the study are expected to show that the use of this traditional art can help students understand the concept of volume in a more contextual and interesting way. In addition, this study also aims to provide alternative learning methods based on local culture, as well as to contribute to innovation in mathematics learning at the elementary school level. Thus, it is hoped that Damar Kurung art can be an effective and relevant learning medium in improving students' understanding of mathematics.